‘Economic constitutionalism in a turbulent world’: a critical review - Andrea Guazzarotti (European Law Open)
The article analyses the book Economic Constitutionalism in a Turbulent World edited by Skordas, Halmai and Mardikian, criticising the assumptions of societal constitutionalism and ordoliberalism on which it is based. The book concurs with the view that the current crisis of global legal institutions cannot be tackled going back to Nation States. Such an assumption seems to be inspired by societal constitutionalism à la Teubner. In contrast to traditional constitutionalism, which hinges on the dichotomy between constituent and constituted power, societal constitutionalism assigns a central role to independent institutions, whose main function is to avoid any hegemony of one social sub-system over another, in particular of politics over economics. The limit of societal constitutionalism lays in its assumption that the economic sub-system has its own rationality that the political–constitutional system can only irritate, taking for granted that the paradigm of that economic rationality is the one established after 1989, thus implicitly adhering to the neo-ordoliberal vision and legitimising its absolute immanentism. Coming to the materiality of the issues underlying the book, most of the contributions conceive globalisation as an engine for the increase of global prosperity. This confidence rests in the Ricardian theory of comparative advantage. However, the latter is valid only under condition of restrictions on the movement of capital. Another assumption made by several contributions is the theory of the varieties of capitalism, according to which individual models of capitalism tend to stabilise around certain production regimes whose key actors are large firms and business associations. According to an alternative, neo-Kaleckian paradigm, there is no natural convergence of the actors of the economic system towards a mutually beneficial institutional set-up, and it is quite unlikely that, without the external intervention of politics, the system can return to equilibrium.